PERTIMBANGAN HAKIM MENJATUHKAN PUTUSAN PIDANA PELAYANAN MASYARAKAT DAN PELATIHAN KERJA TERHADAP PELAKU DILIHAT DARI SISI KEADILAN BAGI KORBAN ANAK (Studi Kasus Putusan No. 11/Pid.Sus-Anak/2022/PN - NIM. A1011201013, SABRYNA AULIA WULANDARI (Fakultas Hukum Universitas Tanjungpura, 2024)
AbstractThis research discusses criminal acts of sexual intercourse committed by children facing the law in the jurisdiction of the Pontianak District Court. Because of the increasing number of cases of sexual intercourse which are not only carried out by adults on child victims, but can also be carried out by child perpetrators. The crime of sexual intercourse is also one of the legal issues that is very important to be studied in depth, because of the increasingly widespread news about sexual intercourse committed against children. Article 76 D of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection regulates sexual relations with children. The problem in this research is the study of decision Number 11/Pid.Sus-Anak/2022/PN.Ptk in terms of the purpose of punishment in the form of Community Service and Job Training, as well as regarding the Appropriateness of Imposing Sanctions in the Form of Community Service in the Pontianak District Court Judge's Decision on Child Offenders If we look at the impact experienced by child victims. The method used in this research is Normative Juridical. The results of this research are that the judge in handing down the Pontianak Court decision did not fulfill the objectives of the sentence. As is known, according to the combined theory of punishment, the purpose of punishment, apart from being educational, also has a deterrent effect because the convict only carries out punishment in the form of Community Service for 120 (one hundred and twenty) hours within a period of 3 months and Job Training for 3 (three) months. So, according to the author, this sentence is still very light, because looking at Article 81 paragraph (1) of Republic of Indonesia Law no. 35 of 2014 concerning Amendments to Republic of Indonesia Law no. 23 of 2002 concerning Child Protection in conjunction with Article 64 Paragraph (1) of the Criminal Code, the maximum sentence is 15 years. So it is very possible that the perpetrator will not feel deterred by the punishment given and will repeat criminal acts, whether similar or other. In handing down a decision, the judge should also consider aspects of the losses experienced by the child victim so that the ultimate goal of punishing children in conflict with the law is that they can reflect, admit the error of their actions and provide a deterrent effect. Where minors who are the targets of the perpetrator's activities experience both physical and intangible losses, where the victim can endure prolonged trauma, where the victim's future can be affected. There needs to be a deeper study of the laws relating to children, so that the process of resolving cases against children by law can run as it should. Keywords: Judge's Considerations, Child Sexual Intercourse, Punishment For Child Perpetrators, Justice For Victims. Abstrak Penelitian ini membahas tentang tindak pidana Persetubuhan yang dilakukan oleh anak berhadapan hukum di wilayah hukum Pengadilan Negeri Pontianak. Karena semakin maraknya kasus persetubuhan yang bukan hanya dilakukan oleh orang dewasa kepada anak korban saja, melainkan juga bisa dilakukan oleh Pelaku anak. Tindak pidana persetubuhan, termasuk juga ke dalam salah satu masalah hukum yang sangat penting untuk dikaji secara mendalam, karena semakin merajalelanya berita mengenai persetubuhan yang dilakukan terhadap anak. Dalam pasal 76 D Undang-Undang Nomor 35 Tahun 2014 Tentang Perubahan Atas Undang-Undang Nomor 23 Tahun 2002 Tentang Perlindungan Anak mengatur tentang Persetubuhan terhadap Anak. Permasalahan dalam penelitian ini adalah kajian putusan Nomor 11/Pid.Sus-Anak/2022/PN.Ptk ditinjau dari sisi tujuan pemidanaan berupa Pelayanan Masyarakat dan Pelatihan Kerja, serta terkait Kesesuaian Penjatuhan Sanksi Berupa Pelayanan Masyarakat pada Putusan Hakim Pengadilan Negeri Pontianak Kepada Pelaku Anak Jika Dilihat Dari Dampak Yang Dialami Korban Anak. Metode yang digunakan dalam penelitian ini adalah Yuridis Normatif. Hasil dari penelitian ini adalah Hakim dalam menjatuhkan Putusan Pengadilan Pontianak kurang memenuhi dari tujuan pemidanaan. Sebagaimana diketahui menurut teori gabungan pemidanaan bahwa tujuan dari pemidanaan selain bersifat mendidik juga menimbulkan efek jera karena terpidana hanya menjalankan Pemidanaan berupa Pelayanan Masyarakat selama 120 (seratus dua puluh) jam dalam kurun waktu 3 bulan dan Pelatihan Kerja selama 3 (tiga) bulan. Sehingga menurut penulis hukuman ini masih sangat ringan, karena melihat dari Pasal 81 ayat (1) Undang